2013
DOI: 10.3109/00207454.2013.816956
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of the influence of CREB1 gene polymorphisms on cognitive dysfunction in Chinese patients with major depression

Abstract: Research has increasingly focused on the role of the cyclic adenosine monophosphate (cAMP) response element binding (CREB) protein in learning and memory, particularly its role in cognitive disorders and neurodegeneration, such as Huntington's disease, Alzheimer's disease, Rubinstein-Taybi syndrome, and Coffin-Lowry syndrome. The cognitive dysfunction of patients with major depressive disorder (MDD), which is widely recognized, is not completely in accordance with depressive severity, and the dysfunction persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…CREB-BDNF pathway is closely related to many neurobiological processes, including synapse and neural plasticity, which may be a potential mechanism for the occurrence and development of depression [ 8 ]. Our present findings are consistent with the findings of previous studies, and verifying the correlation between CREB1 and depression in Chinese people [ 7 , 27 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…CREB-BDNF pathway is closely related to many neurobiological processes, including synapse and neural plasticity, which may be a potential mechanism for the occurrence and development of depression [ 8 ]. Our present findings are consistent with the findings of previous studies, and verifying the correlation between CREB1 and depression in Chinese people [ 7 , 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous work has shown that the rs2253206 and rs10932201 in CREB1 and rs162209 in GRM7 may light on the pathogenesis of depression [ 7 , 26 , 27 ]. However, there are few reports on the genetic susceptibility of CREB1 SNPs rs2253206 and rs10932201 and GRM7 SNPs rs162209 involved in depression.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs in the CREB1 gene, including rs2253206, have previously been significantly associated with traits linked to cognitive vulnerability. Guo et al (2014) investigated the effect of CREB1 gene polymorphisms on cognitive dysfunction in Chinese patients with major depression and their results suggest the CREB1 gene is a promising marker for cognitive function in major depression patients. Juhasz et al (2011) investigated risk factors for depression, and while studying the neuroplastic pathway, they demonstrated a significant association between the CREB1 rs2253206 polymorphism with rumination and severe depression, reporting that minor allele carriers are less likely to ruminate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies focusing on depression, schizophrenia, rumination, and negative emotionally related memory impairments have found significant associations with CREB regulation (Kawanishi et al, 1999; Barrot et al, 2002; Lazary et al, 2011; Guo et al, 2014). Genetic polymorphisms can influence the expression of linked loci.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Moreover, cognitive impairment is thought to be an intrinsic characteristic of MDD that may take precedence over depressive symptoms. [19][20][21][22] Despite such extensive studies, the pathological mechanisms of cognitive deficits in MDD remain uncertain.…”
Section: Introductionmentioning
confidence: 99%